Synthesis of novel high performance Polyurethane nanocomposites from castor oil as renewable Polyol : study on mechanical, thermal and barrier properties - Alaa Mashjel, Ali (2015)
Polyurethane nanocomposite is one of the promising materials and attracts many researchers to explore its potential. This work is aimed to develop a series of polyurethanes (PUs) based on castor oil with polyols as a renewable resource incorporated with different types of nano-fillers (organic and inorganic) to study the improved physico-chemical behaviour of novel polyurethanes fabricated with organically modified clay and purified Multi-Walled Carbon Nanotubes (MWCNTs) nanofillers; forming nanocomposites film by an in-situ polymerization technique and assisted by ultrasonication mixed at various times. Toluene diisocyanate (TDI) and chain extender 1, 4-butane diol (BDO) were employed with polyols to produce COPUs- (Cloisite 30B / MWCNTs) nanocomposites. The amount of nanofillers was varied from 0% to 5% wt for Cloisite 30B and for MWCNTs, the nanofillers range from 0% to 1% wt. The synthesized PU nanocomposites were characterized for different physical properties such as mechanical and morphology changes, oxidative thermal stability as well as sample purity and surface area studies using the Fourier Transform Infrared Spectroscopy (FTIR), the Field Emission Scanning Electron Microscopy (FESEM), X-ray diffraction (XRD), Thermogravimetric analysis (TGA) and Differential Scanning Calorimetry (DSC). Surface area was studied using the Brunauer-Emmet-Teller (BET) technique and elemental ratios were investigated using energy dispersive X-ray analysis (EDX) with the attached equipment in FESEM spectroscopy. The barrier properties were investigated by looking at nitrogen permeability measurements using a membrane separation unit. The thermal and mechanical properties of the COPUs matrix were found significantly improved with the incorporation of organoclay and MWCNTs. The purified MWCNTs were proven to have higher compatibility compared to organoclay in polymer matrix at even low concentrations of MWCNTs (0.3%), as results achieved presented higher d spacing, mechanical and thermal properties as shown in different instrumental analyses compared to its counterpart, organoclay (3 wt %). Tensile properties showed an improvement of ~ 324% in tensile strength and a decrease of ~74% in elongation at break with 5 wt% organoclay, while COPUs - MWCNTs nanocomposites depicted a massive development in tensile strength and lowering down of elongation at break with 1wt% (~640% and ~ 80%). Thermal properties depicted an increase of 10-30 oC in COPUs–C30B nanocomposites, while a significant increase of degradation temperature (~ 50 oC) was observed in 0.3 wt% of MWCNTs in the COPUs matrix. A major permeability reduction (~25 % and ~ 50%) was attained with 5 wt% of organoclay and 0.5 wt% MWCNTs loaded nanocomposites, compared to pure COPUs. The optimization study was conducted using a response surface methodology (RSM) which included the Central composite design (CCD) with three factors; temperature, time and the amount of nanofillers. An increase in temperature and nanofillers amount favoured the nanocomposites polymerization up to a certain extent. The optimum tensile strength obtained was 1.997 MPa at temperature 90 oC and wt% 4.99% for clay and 2.207 MPa at temperature 90 oC and wt% 1% for MWCNTs respectively.